Effects of climate change on soils of cattle regions from the southern karst plain Habana - Matanzas, Cuba - Febles González, J. M.; Somoza Cabrera, J.; Vega, Marina B.; Amaral Sobrinho, N.; Calderín García, A.; Febles Díaz, J. M. (Cuban Journal of Agricultural Science, 2017)
Currently, the effects of climate change lead to widespread processes of soil degradation in cattle regions, with serious environmental, social and economic consequences. This have especially significant in the karst regions of western Cuba, which coincides with the areas of highest agricultural production, population density and the most important water supply basins of several provinces. Based on researches carried out for more than three decades in reference livestock farms, and through a combination of qualitative and quantitative data, this article exposes the effects of intensive anthropogenesis and climate change on the spatial - temporal evolution of soil properties. Among them, the reduction of organic matter content, pH increase, compaction values with apparent density thresholds higher than 1.34 Mg.m-3, reinforcement of karstic-erosive processes, salinization, and others that coexist zonally and spatially in an essentially superficial domain (A + B0-50 cm), with a marked tendency to increase. These results should be interpreted as an indispensable basis for the design of mitigation and adaptation strategies with an agro-ecological approach in regions of Cuba. Key words: erosion, sustainability, karst regions.